Design and Implementation of the Attitude, Ethics and Communication Module -Working in a Healthcare Team in a Medical Institute - Shetty, Archana; Sandeepa, Surpiya; Minal, Jessica; Murali, Nirupama (Journal of College of Medical Sciences-Nepal, 2021)
Background Communication and inter-personal skills are an imperative requirement in undergraduate medical curriculum. Incorporation of Attitude, Ethics and Communication module (AETCOM) was a major change in the new curriculum implemented by National Medical Commission (NMC) of India in 2019. Implementing modules related to soft skills like “Working in a healthcare team” come with challenges and novel learning experiences for the medical faculties. Methods This prospective cross-sectional study was conducted in the department of Pathology at a medical college institute over a period of four months. AETCOM module “Working in a healthcare team” was to be taken over a duration of six hours on every Saturday 8:00 to 9:00 am consecutively for six weeks. Two hours were taken as small group discussions and four hours as class room based planned interview sessions with under recognized personnel of healthcare team – billing, housekeeping staff, junior residents, and technicians Results A brief outline of the entire module was conveyed in the first small group session. Subsequent interview sessions were divided into icebreaking, interview and concluding sessions. In the last small group session, students were asked to give feedback and write the narrative reflective writing in their log books as a formative assessment. The students liked interview session of housekeeping personnel the most. Conclusions We wish to share our experience of designing and implementing this module which not only gave students a preview into contribution of various personnel in daily patient care but also stressed upon the need for developing an attitude of respect and good communication.